THE PERAN KOMITE SEKOLAH SEBAGAI PERANTARA ANTARA LEMBAGA PENDIDIKAN DAN MASYARAKAT DESA DI MADRASAH TSANAWIYAH KECAMATAN GABUS KABUPATEN GROBOGAN - Saekul Anwar (Jurnal Administrasi Negara, 2022)
This study aims to analyze and describe the role of school committee as a mediator or intermediary between educational institutions and village communities in Gabus Sub-District, Grobogan Regency, Central Java. This research was conducted in Madrasah Tsanawiyah in Gabus Sub-District, Grobogan Regency. The research used qualitative method with phenomenological approach. The informants selected using purposive sampling technique and data collected by interviews. The data analysis technique used inductive thinking framework analysis. The Findings indicate that the school committees at Madrasah Tsanawiyah in Gabus sub-District, Grobogan Regency, have carried out its duties properly according to the law's mandate, namely as an advisory, supporting, mediating and controlling agency in the administration of education at the secondary level. There are still some obstacles faced in optimizing their role, especially in fulfilling the administrative completeness of the school committee's organization. The existince of school committees as new institutions will certainly make alteration and maybe even spur some conflicts and innovations at the school level. The school committee has not been fully optimized by the education unit and the surrounding community in improving the quality of education in their environment.